2013
DOI: 10.2337/dc13-1048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Postmenopausal Status and Age at Menopause on Type 2 Diabetes and Prediabetes in Japanese Individuals: Toranomon Hospital Health Management Center Study 17 (TOPICS 17)

Abstract: OBJECTIVEFindings on the effect of menopause or age at menopause on the presence of hyperglycemia are controversial, and why women after menopause have a higher probability of having hyperglycemia than men in the same age range remains unknown.RESEARCH DESIGN AND METHODSWe reviewed data on 29,189 men, 6,308 premenopausal women, and 4,570 postmenopausal women in Japan. Odds ratios (ORs) for diabetes or prediabetes indicated by American Diabetes Association criteria were calculated for men and for pre- and postm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
78
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 39 publications
3
78
1
Order By: Relevance
“…The first conclusion of our study was that the postmenopausal state was significantly associated with dysglycemia independently of normal aging, although the increased probability in postmenopausal women did not equal that in men (2). We mentioned that the prevalence of diabetes was reported to be lower in women than in men aged 60 years or younger, whereas women in their 60s and 70s were more likely to have diabetes than men of the same age based on data from the International Diabetes Federation and a study from China (3).…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…The first conclusion of our study was that the postmenopausal state was significantly associated with dysglycemia independently of normal aging, although the increased probability in postmenopausal women did not equal that in men (2). We mentioned that the prevalence of diabetes was reported to be lower in women than in men aged 60 years or younger, whereas women in their 60s and 70s were more likely to have diabetes than men of the same age based on data from the International Diabetes Federation and a study from China (3).…”
mentioning
confidence: 69%
“…We thank Akter et al (1) for their interest in our study (2). While we agree that the mean age was higher in the postmenopausal women than in the premenopausal women, results of our additional analysis of the 10,878 women showed that independently of older age ($50 years) and demographic and metabolic factors (BMI, parental history of diabetes, physical activity habit, smoking habit, hypertension, log-transformed triglycerides, and HDL cholesterol) the postmenopausal state was associated with a 1.50 (95% CI 1.30-1.74) higher probability of the presence of dysglycemia (either type 2 diabetes or prediabetes) compared with premenopausal women.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…We read with great interest the article by Heianza et al (1), which showed a higher probability of type 2 diabetes and prediabetes among postmenopausal women than among premenopausal women. It is also suggested that menopause and older age might additively influence the elevated probability of type 2 diabetes.…”
mentioning
confidence: 88%
“…We hope this article provides additional clarification regarding the ultimate goals of Heianza et al (1) and calls for further studies looking into whether menopausal status independently influences diabetes risk.…”
mentioning
confidence: 99%